Rice Knowledge Management Portal for Technology Dissemination: A Case Study for Haryana, Punjab and Uttarakhand States (Indian Journal of Extension Education, 2013)
Information and Communication Technology (ICT) breakthroughs have brought new opportunities to restructure the knowledge transfer environment. ICT technology has opened new avenues and brought new challenges to the end users. The Knowledge Management (KM) practices using Information & Communication Technology (ICTs) has emerged as fastest viable solutions to the knowledge transfer mechanism over the traditional system, where information sharing mechanisms appear to be inadequate. In Asia, rice is not only the staple food, but also constitutes the major economic activity and a key source of employment and income for the rural population. Data, information and knowledge differ from one rice growing region to another. Knowledge varies between contexts and emerges from the flow of information around the system. In multiple stakeholders of the rice value chain, the interaction between the data, information and knowledge gets much complicated and requires a more sophisticated approach. Keeping in view the potentials of ICT applications, an attempt has been made to develop a portal for knowledge dissemination. The Rice Knowledge Management Portal (RKMP) has been envisaged to enable rice workers to create, manage and share scientific, technical and market-related information for the benefit of all stakeholders. This portal helps to strengthen communication and provides a platform for collaborative action and information sharing among various key players and stakeholders in the rice sector. The portal deals with the concepts of knowledge dissemination options using Information & Communication Technology. The RKMP portal (http://rkmp. iari.res. in) is a getaway for providing rice knowledge to the stakeholders. The portal consists of several information systems and decision support modules to give a unified solution for a particular query. A case study has also been taken for states of Haryana, Punjab and Uttarakhand by integrating the state specific content collected from these states. The portal provides many specific queries for rice research and cultivation, such as queries related to variety selection, management of disease, insect, pest of rice, rice statistics, site specific frequently asked questions (FAQ).